2017
DOI: 10.25165/j.ijabe.20171005.3079
|View full text |Cite
|
Sign up to set email alerts
|

Downwash distribution of single-rotor unmanned agricultural helicopter on hovering state

Abstract: The effective coverage and velocity of downwash are directly related to the assemblage of spraying system and spraying effect. The downwash of the unmanned agricultural helicopter (UAH) N-3 was discussed in the paper. The computational fluid dynamics (CFD) methods were used to simulate and analyze the distribution of the downwash, and a wind field measurement device had been designed to test the downwash of UAH N-3. In the tests, the UAH N-3 was raised up to 5.0 m, 6.0 m and 7.0 m from the ground, "annular-rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…As single-rotor UAVs or helicopters have only one propeller and may be relatively simple to complete simulation, the CFD research about them was increased from 2017. Zhang et al used CFD simulation combined with real hovering trials to obtain the characteristics of droplet distribution of N-3 [51] . Yang et al simulated the distribution model of the rotor of XV-2.…”
Section: Examination By Using Cfdmentioning
confidence: 99%
“…As single-rotor UAVs or helicopters have only one propeller and may be relatively simple to complete simulation, the CFD research about them was increased from 2017. Zhang et al used CFD simulation combined with real hovering trials to obtain the characteristics of droplet distribution of N-3 [51] . Yang et al simulated the distribution model of the rotor of XV-2.…”
Section: Examination By Using Cfdmentioning
confidence: 99%
“…Helicopter sprayers have long been employed in agricultural operations, particularly in medium to large-scale farms and hard to reach terrain. These aerial platforms offer certain advantages over traditional ground-based sprayers because of their ability to cover large areas quickly with excellent maneuverability, besides being capable of delivering a concentrated spray directly to the target area (Zhang et al, 2017;Seo & Umeda, 2021).…”
Section: Drones and Helicopters Airplanes And Traditional Sprayersmentioning
confidence: 99%
“…The reduction in nozzle spray angle is known to be highly correlated with an increase in air velocity past a nozzle. Songchao et al [53] used a single rotor unmanned helicopter to study downwash distribution using a computational fluid dynamics model and found that the downwash covered an area equivalent to the rotor radius of 3.0 m in size with a boundary velocity of 0.5 m•s −1 . This appears to indicate that the downwash effect extends beyond the immediate vicinity of the aircraft.…”
Section: Fluorescent Droplets On Weed Leavesmentioning
confidence: 99%